The Demand for Multilingual Human Capital in the U.S. Labor Market. (28th February 2017) - Damari, Rebecca Rubin; Rivers, William P.; Brecht, Richard D.; Gardner, Philip; Pulupa, Catherine; Robinson, John
Abstract: This article presents the results of a 2014 survey of more than 2, 100 U.S. employers on their requirements for multilingual employees. The survey found a significant discrepancy: On the one hand, 93% of respondents "value[d] employees who…are able to work effectively with customers, clients, and businesses from a range of different countries and cultures." On the other, 66% of respondents reported identifying foreign language skills in the hiring process, 41% reported giving advantage to multilingual applicants, and only 10% of respondents indicated that new hires "needed to speak at least one language besides English." In addition, the survey revealed employer characteristics related to demand for language ability: Industries with the greatest demand were government and public administration, information services, educational services, health care, and the administrative sector. Language skills were sought in combination with other skill sets, notably customer service, sales, vendor management, and marketing. Finally, the survey identified college majors sought in conjunction with foreign language ability. The study is unique in its size; its coverage of small, medium, and large businesses; and its focus on college recruitment and hiring. The results are critical to educational programs seeking to understand the value of language in the job market